A percepção de terapeutas ocupacionais da saúde mental sobre os cuidados paliativos - GOMES, Alanna Julie Leão Ferreira (2023)
Mental Disorders are defined as syndromes characterized by a clinically expressive cognition disturbance. Moreover emotional regulation and behavior, reflecting a dysfunction in their psychological, biological, or developmental processes of mental functioning. These disorders are usually linked to significant suffering and disability involving such as social activities, professionals and other relevant activities. There is solid evidence pointing to mental suffering as one of the most prevalent health problems. For these reasons, we can say that Mental Disorders need special attention, especially for more permanent diseases. Thus, taking into consideration the chronic and debilitating characteristics, it is chosen as a good strategy of care, Palliative Care, according to its preception, it can be offered to every individual that possesses such aspects. This project highlighted Schizophrenia, Bipolar Affective Disorder and Drug Addict Disorders, which have been chosen to be mental illnesses that demonstrate the characteristics described as chronic and disabling. The presente study is qualitative, descriptive and exploratory study and aims to investigate whether occupational therapists characterize their action as palliative actions in mental health, as well as investigate whether occupational therapists believe that mental health patients are eligible for Palliative Care. To check which aspects of these professionals are palliative actions, to verify how this subject is teaching in the curricular formation and to evaluate how much occupational therapists know about the work in Palliative Care. In this sense, the importance of the study is verified since there is still a small arsenal of scientific knowledge that disassociates palliative care from the terminality of life and also takes into account the chronic conditions that can not be cured but that are controllable aspects, such as mental disorders.